Tradução automática de problemas de escalonamento job shop flexível com bloqueio para autômatos utilizando a teoria de controle supervisório - Daniel Sarsur Câmara (2020)
This work is an exploratory study that aims to develop an algorithm to automatically translate a Blocking Flexible Job Shop Scheduling Problem modeling into automata using the Supervisory Control Theory. The mechanism for interpretation of literature problem data and the methodology for generating automata that represent the behavior and constraints of the problem are presented. In addition, the closed-loop behavior of some systems is found, on which a makespan minimization heuristic is applied. The results found are close to those in the literature. An algorithm for obtaining strings of events that minimize production times in a flexible manufacturing system with stochastic demands is also developed.